Tinjauan Teori Sadd Al-Dzari'ah Terhadap Upaya Hakim Wanita di Pengadilan Agama Samarinda dan Pengadilan Agama Tenggarong dalam Menjaga Keharmonisan Rumah Tangga - Sabrina, Putri; Hervina, Hervina; Fitriyanti, Vivit (FASYA Press, 2022)
Abstract Judges as one of the professions that have mutation regulations. The implementation of the transfer of judges is regulated in the Decree of the Chief Justice of the Supreme Court (KMA) of the Republic of Indonesia Number: 48/KMA/SK/II/2017 concerning the renewal of the pattern of promotion and transfer of judges in four court environments. These regulations can lead to long-distance marriage relationships for judges who are already married, this raises many challenges and obstacles related to household harmony. Especially for female judges who are married, they must carry out many roles, both as wives, mothers for their families and law enforcement in Indonesia. Based on these problems, the purpose of this study was to find out the opinions of female judges at the Samarinda and Tenggarong Religious Courts regarding the concept of a harmonious family, then to find out the efforts of female judges at the Samarinda and Tenggarong Religious Courts in maintaining household harmony, and to find out a review of sadd al-dzariah theory. to the efforts of female judges at the Samarinda and Tenggarong Religious Courts in maintaining household harmony. This research is a type of qualitative research with a normative empirical approach. The subjects in this study were female judges at the Samarinda Religious Court and the Tenggarong Religious Court who were married, while the object in this study was the efforts of female judges in maintaining household harmony. Data collection techniques used are interviews and documentation. The data analysis technique used is qualitative analysis with the steps of data collection, data reduction, data processing, and drawing conclusions. The results that can be obtained from this study are the opinion of female judges regarding the concept of a harmonious family, which is a family that has a strong commitment to maintaining the integrity of the household, there is mutual trust, openness, honesty, good communication, problems are solved together and there is an attitude of acceptance. criticism and self-improvement. Efforts made by female judges to maintain household harmony are: adhering to religion, respecting, appreciating and understanding, good communication, quality time, being open and trusting, solving problems together, guarding actions or words that can offend husbands. and keep away from things that are feared will lead to bad consequences. A review of sadd al-dzariah theory on the efforts of female judges at the Samarinda and Tenggarong Religious Courts in maintaining household harmony, namely that these efforts are in line with the sadd al-dzarî'ah concept and in line with Islamic law. Keywords: Efforts of Female Judges, Household Harmony, Sadd Al-Dzari'ah